Beyond Postmodernism : Onto the Postcontemporary. - Brooks, Christopher K. (Cambridge Scholars Publishing, 2013)
Beyond Postmodernism: Onto the Postcontemporary is a collection designed to provide the reader with an alternative to viewing the world through the lens of Postmodernism. Contributors to this collection utilize and define such critical tools as transhumanism, post-post theory, posthumanism, and postcontemporary theory. Other essays focus on interpreting texts or genres, yielding impressive conclusions that were ""beyond"" the scope of postmodern discourse. Eclectic in nature, while examining wo ...